2017
DOI: 10.1016/j.ccm.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Pneumonia in Patients with Hematologic Malignancy and Hematopoietic Stem Cell Transplantation

Abstract: Synopsis Fungal pneumonias cause unacceptable morbidity among patients with hematologic malignancies (HM) and recipients of hematopoietic stem cell transplantation (HSCT). The high incidence of fungal pneumonias in HM/HSCT populations arises from their frequently severe, complex and persistent immune dysfunction caused by both the underlying disease and its treatment. The cytopenias, treatment toxicities and other immune derangements that make HM/HSCT patients susceptible to fungal pneumonia frequently also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 121 publications
0
21
0
1
Order By: Relevance
“…The treatment also leads to a longer risk of neutropenia and a higher risk of fungal pneumonia. Neutropenia, which is usually caused by chemotherapy or radiotherapy, is a major risk factor for bacterial and fungal lung infections [ 5 ]. Similarly, in this study, the Incidence of neutropenia was found to be higher in patients with fungal pneumonia than in non-fungal pneumonia patients (80% vs. 53%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment also leads to a longer risk of neutropenia and a higher risk of fungal pneumonia. Neutropenia, which is usually caused by chemotherapy or radiotherapy, is a major risk factor for bacterial and fungal lung infections [ 5 ]. Similarly, in this study, the Incidence of neutropenia was found to be higher in patients with fungal pneumonia than in non-fungal pneumonia patients (80% vs. 53%).…”
Section: Discussionmentioning
confidence: 99%
“…Both innate and adaptive immune functions are suppressed by the cancer itself and chemotherapeutic agents. Fungal pneumonia is common in patients with hematological cancer due to mucosal damage caused by cytotoxic chemotherapies and steroids, neutropenia and leukocyte defects, hematopoietic stem cell transplantation (HSCT) and subsequent immunosuppressive agents used for the treatment of graft versus host disease (GVHD) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial pneumonias are also common and may occur as a co-infection or secondary infection with a respiratory virus. Fungal and other opportunistic infections such as Pneumocystis jirovecii must also be considered [42]. As in immunocompetent patients, treatment of ARDS centers on treatment of the underlying cause while providing supportive care with low tidal volume mechanical ventilation.…”
Section: Respiratory Viral Infection Is Common Aftermentioning
confidence: 99%
“…IPS is thought to affect up to 15% of patients after myeloablative allogeneic HSCT, and only ~ 2% of patients after non-myeloablative HSCT. Median time of onset of IPS [35,42] is 19 days after HSCT and mortality ranges from 60-80% in all patients, with nearly 100% mortality if mechanical ventilation is required [58]. Though the pathophysiology of IPS is incompletely understood, research indicating a pathogenic role for TNF-α has led to the use of the anti-TNF-α antibody etanercept to treat IPS, with mixed clinical results [59][60][61][62].…”
Section: Respiratory Viral Infection Is Common Aftermentioning
confidence: 99%
“…In patients with profound (ANC < 500) and/or prolonged duration of neutropenia (>10 days), in addition to the above mentioned etiologies, fungal pathogens should be strongly considered [12]. Aspergillus fumigatus is the most common fungal pathogen causing pneumonia in this patient population.…”
Section: Fungal Pathogensmentioning
confidence: 99%